Over-rotated Rieger flap for a large lateral nasal tip defect reconstruction - De Piano, Ernesto; Rubegni, Pietro; Falcinelli, Francesca (Dermatology reports, 2024)
A 65-year-old man presented with a Melanoma in situ of the nasal tip. Complete excision was achieved after 2 “Slow Mohs” stages, resulting in a circular 2.7 X 2.4 cm defect involving the right lateral nasal tip, dorsum and sidewall and extending to the perichondrium.